Ultrasound Imaging of Mouse Fetal Intracranial Hemorrhage Due to Ischemia/Reperfusion - Funamoto, Kenichi; Ito, Takuya; Funamoto, Kiyoe; Velayo, Clarissa L.; Kimura, Yoshitaka (Frontiers in Physiology, 2017)
Despite vast improvement in perinatal care during the 30 years, the incidence rate of neonatal encephalopathy remains unchanged without any further progresses towards preventive strategies for the clinical impasse. Antenatal brain injury including fetal intracranial hemorrhage caused by ischemia/reperfusion is known as one of primary triggers of neonatal injuries. However, the mechanisms of antenatal brain injury are poorly understood unless better predictive models of the disease are developed. Here we show a mouse model for fetal intracranial hemorrhage in vivo developed to investigate the actual timing of hypoxia-ischemic events and their related mechanisms of injury. Intrauterine growth restriction mouse fetuses were exposed to ischemia/reperfusion cycles by occluding and opening the uterine and ovarian arteries in the mother. The presence and timing of fetal intracranial hemorrhage caused by the ischemia/reperfusion were measured with histological observation and ultrasound imaging. Protein-restricted diet increased the risk of fetal intracranial hemorrhage. The monitoring of fetal brains by ultrasound B-mode imaging clarified that cerebral hemorrhage in fetal brain occurred after the second ischemic period. Three-dimensional ultrasound power Doppler imaging visualized disappearance of main blood flows in the fetal brain. These indicate a breakdown of cerebrovascular autoregulation cause the fetal intracranial hemorrhage. This study supports the fact that the ischemia/reperfusion triggers a cerebral hemorrhage in a fetal brain. The present method enables us to noninvasively create the cerebral hemorrhage in a fetus without directly touching the body but with repeated occlusion and opening of the uterine and ovarian arteries in the mother.